Pengaruh Lingkungan Keluarga Terhadap Pembentukan Tingkah Laku Anak - Marfuatun Marfuatun; Yosi Nur Kholisho; Nisa Afifah (Educatio, 2021)
Education through activities outside of school is a learning activity that does not require tiered and continuous activities. The family is the main foundation that can influence the attitudes and behavior of a child. Children's behavior includes attitudes, speech, actions and perceptions of children in the process of development so that they become a character. The character appears through thoughts obtained based on experience and observations from where a person grows and develops, starting from the first meaning that is understood based on a person's words, gestures and behavior. The purpose of this study was to determine the influence of the family environment on the formation of children's character. The method used is descriptive quantitative, with a correlational study approach. After testing the hypothesis which reads: 'there is an influence of the family environment on the formation of children's behavior', it was found that the hypothesis is acceptable, meaning that the family environment has an effect of 13.8%. These results indicate that there is an influence of the family environment on the formation and changes in children's behavior, the family is the initial foundation for children to interact with the outside environment, both the living environment and the school environment.